2023 activity of Nyamulagira volcano monitored by SAR interferometric coherence - Marco Polcari; Emanuele Ferrentino; Charles Balagizi; Diego Coppola; Sébastien Valade (Science of Remote Sensing, 2025)
In this work the multi-temporal InSAR coherence is exploited to analyze several phenomena during the 2023 Nyamulagira volcano activity in the Democratic Republic of Congo. Starting from March 2023 a significant increasing of the activity was observed with several eruptions and a lava lake inside the northeastern crater pit. SAR data acquired from January to December 2023 by Sentinel-1 missions were exploited to follow the temporal evolution of the volcanic activity by the analysis of any InSAR coherence variations. The aim is to detect any lava flows inside the caldera and overflowing the flanks of the volcano. In addition, the time needed for the lava to solidify is tentatively estimated by studying the statistical behavior of the coherence pattern ascribable to a lava flow. Experimental results show a significant lava effusion inside Nyamulagira caldera from the beginning of March, while in mid-May the increase of the activity induced an overflowing from the caldera, with a lava flow observed along the NW flank of the volcano. Then, starting from the end of May-early June, the activity started to return to low levels. The statistical analysis of the probability distributions suggest that after the crisis of May, the lava emitted during the eruption, follows a solidification and likely cooling phase with an approximate time to complete the process estimated in 45/50 days. These results were synergistically used with other data to support the GVO local monitoring team in managing the May 2023 Nyamulagira volcano crisis.